Structural and selective gas adsorption studies of polyoxometalate and tris(ethylenediamine) cobalt(III) based ionic crystals - Dey, Chandan; Das, Raja; Pachfule, Pradip; Poddar, Pankaj; Banerjee, Rahul (Crystal Growth & Design, 2011)
Seven new ionic solids built on polyoxometalate anions and [Co(en)(3)](3+) cations, namely, [Co(en)(3)Mo(8)O(26)(H(3)O)-(Cl)](DMF)(4)(H(2)O) (Co-Mo(8)-DMF), [alpha-PW(12)O(40)][Co(en)(3)]center dot 6DMF (Co-W(12)P-DMF), [alpha-PW(12)O(40)][Co(en)(3)]center dot 6DEF (Co-W(12)P-DEF), [alpha-PMo(12)O(40)][Co(en)(3)]center dot 5.5DMF (Co-Mo(12)P-DMF), [alpha-PMo(12)O(40)][Co(en)(3)]center dot 6DEF (Co-Mo(12)P-DEF), [alpha-SiW(12)O(40)]-[Co(en)(3)](3/2)[Cl](1/2)center dot 6DMF center dot 3H(2)O (Co-W(12)Si-DMF), and [alpha-SiW(12)O(40)][Co(en)(3)]center dot 6DEF (Co-W(12)Si-DEF), have been synthesized from nonaqueous (DMF/DEF) media and characterized by single-crystal X-ray diffraction. We attempt to understand if [Co(en)(3)](3+) cations used in these reaction systems play a crucial role in controlling the assembly of these crystals. These ionic solids, after removal of the DMF or DEF molecules, are found to exhibit size selective H(2) adsorption properties over N(2). The amount of hydrogen adsorption was influenced by POM anion types and their orientations. CoMo(12)P-DEF has the highest (0.9 wt %) H(2) uptake, and CoW(12)P-DEF has the lowest (0.4 wt %) uptake among the series when the adsorbate pressure approached 1 atm.